KAJIAN POTENSI USAHA PEMBUATAN TERASI UDANG STUDI KASUSDESA BANTELAN, KECAMATAN BATU PUTIH, KABUPATEN SUMENEP - Iffan Maflahah (AGROINTEK, 2013)
Bantelan is one of coastal village in the Batu Putih , Sumenep, known as shrimp paste where made. More than 50 families (head of household ) has a side business for shrimp paste made. Based on this fact, indicating in Bantelan has a potential area for the development of shrimp paste made. Purposes these research were : 1) determine the potential of making shrimp paste in Bantelan; 2) assessing manufacturing process and marketing distribution; 3) assessing the potential of shrimp paste development. Research methodology is observation and interviews with shrimp paste makers in Bantelan. Results showed : 1) Bantelan has the potential to be business processing shrimp paste; 2) shrimp paste processing still using simple technology; 3) product quality need improvements as technology, capital, marketing and quality for the development of business scale.